The lastling - Gross, Philip (Clarion Books, 2006)
While hunting for rare and endangered species with her uncle in the Himalayas, fourteen-year-old Paris learns about humanity and friendship from Tahr, a twelve-year-old Buddhist monk who is trying to protect a young yeti.